Hate speech against the LGTBIQ+ community and its representation in Veneno series - Martínez de Bartolomé Rincón, Ireide; Rivera-Martín, Beatriz (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
The objective of this research is the critical analysis of the speech contained in the eight episodes of the only season of the Spanish series Veneno. To carry out this research, we have chosen a methodology based on the analysis of derogatory and offensive language towards the main characters of the plot, which will be classified into three categories of language and expressions: homophobic discourse (directed towards LGBTQ+ people), discourse of social rejection (towards people, groups and allied institutions) and hate speech (constituting a crime).